2005
DOI: 10.1111/j.1460-9568.2005.04071.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor 1‐immunopositive neurons in the gliotic CA1 area of the mouse hippocampus after pilocarpine‐induced status epilepticus

Abstract: Significant reduction in glutamate receptor 1 (GluR1)- and GluR2/3-immunopositive neurons was demonstrated in the hilus of the dentate gyrus in mice killed on days 1, 7 and 60 after pilocarpine-induced status epilepticus (PISE). In addition, GluR1 and GluR2/3 immunostaining in the strata oriens, radiatum and lacunosum moleculare of areas CA1-3 decreased drastically on days 7 and 60 after PISE. Neuronal loss observed in the above regions may account, at least in part, for a decrease in GluR immunoreactivity. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 50 publications
19
34
0
Order By: Relevance
“…In the hilus of the dentate gyrus of aged DAL mice, the neurons were also decreased (Table 1). Neuronal loss in the CA1 area of DAL mice was confirmed by immunostaining with antiNeuN antibody (Tang et al, 2005) (Fig. 4 E-H ).…”
Section: Aldh2 Deficiency By Itself Induces Age-dependent Brain Degenmentioning
confidence: 90%
“…In the hilus of the dentate gyrus of aged DAL mice, the neurons were also decreased (Table 1). Neuronal loss in the CA1 area of DAL mice was confirmed by immunostaining with antiNeuN antibody (Tang et al, 2005) (Fig. 4 E-H ).…”
Section: Aldh2 Deficiency By Itself Induces Age-dependent Brain Degenmentioning
confidence: 90%
“…In this model, days to weeks (with average latent period of 14.4±11.9 days) following an episode of pilocarpine induced status epilepticus, animals begin having spontaneous recurrent seizures and continue to have seizures for life [16,[73][74]. Many of the pathophysiological changes observed in epileptic human brain tissue have been shown to be present in pilocarpineinduced epileptic mice, including hippocampal neuronal death, sclerosis and axon reorganization, in particular, mossy fiber sprouting [64][65]. Behavioral and cognitive changes occur soon after pilocarpine induced status epilepticus [33,41,59,61,77].…”
Section: Agonists and Antagonists Of Mglurs As Candidate Drugs To Prementioning
confidence: 99%
“…In the rat kindling *Address correspondence to this author at Epilepsy Research Lab, National Neuroscience Institute, 11 Jalan Tan Tock Seng, Singapore; Tel: (65) 63577128; Fax: (65) 62569178; E-mail: Feng_Ru_Tang@nni.com.sg model, an initial up regulation in mGluR1mRNA in the dentate gyrus, CA3, and CA4 areas, and down regulation in mGluR5 mRNA in CA4, CA1, CA3 areas and dentate gyrus of the hippocampus were observed 24 h after the last kindled seizure. By 28 days, mGluR1 mRNA levels had returned to control levels, however, mGluR5 mRNA level was still lower than the control, suggesting that the mRNAs for mGluR1 and mGluR5 are differentially regulated by kindling, and may contribute to kindling epileptogenesis [1].…”
Section: Changes Of Mglurs In Animal Model Of Seizures Status Epilepmentioning
confidence: 99%
“…There was a considerable elimination of PCs in CA3c in 17% of the PILO-responsive NMRI, whereas these cells seemed to remain intact in the Balb/c mice. This difference is in line with several papers reporting that (1) Balb/c-related strains were found to be resistant to PILO-induced SE (Schauwecker 2012), and (2) the descendants of the so called Swiss mice, a separate genealogical line (Beck et al 2000), including the NMRI strain, were found to suffer severe damage to the CA3 PCs (Turski et al 1984;Riban et al 2002;Tang et al 2005). …”
Section: Effects Of Seizures On Pyramidal Cellssupporting
confidence: 88%
“…13. C, E), which were suggested to be MCs (Tang et al 2005). It is worth noting that the layer-to-layer analysis of the semiquantitative data of the two mouse strains revealed significant density differences in the GluA2 immunoreactivities of the DG.…”
Section: Ampa Receptor Subunitsmentioning
confidence: 87%